Enabling Seamless Access to Digital Graphical Contents for Visually Impaired Individuals via Semantic-Aware Processing. (15th November 2007) - Wang, Zheshen; Xu, Xinyu; Li, Baoxin
Abstract : Vision is one of the main sources through which people obtain information from the world, but unfortunately, visually-impaired people are partially or completely deprived of this type of information. With the help of computer technologies, people with visual impairment can independently access digital textual information by using text-to-speech and text-to-Braille software. However, in general, there still exists a major barrier for people who are blind to access the graphical information independently in real-time without the help of sighted people. In this paper, we propose a novel multi-level and multi-modal approach aiming at addressing this challenging and practical problem, with the key idea being semantic-aware visual-to-tactile conversion through semantic image categorization and segmentation, and semantic-driven image simplification. An end-to-end prototype system was built based on the approach. We present the details of the approach and the system, report sample experimental results with realistic data, and compare our approach with current typical practice.